Tantangan Integrasi Sosial Imigran di Indonesia: Perspektif Ekonomi dan Keamanan - Delyano, Farel Bima; Mirwanto, Tony; Arief Hamdi, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study analyzes the challenges of immigrant social integration in Indonesia through a qualitative literature review approach. The focus lies on two interconnected dimensions, namely economics and security, which significantly shape the success of the integration process. From an economic perspective, immigrants often face restricted access to formal employment, dependence on informal sectors, and reliance on humanitarian aid, which limit their ability to adapt and reinforce perceptions of burden among local communities. From a security perspective, their presence is frequently associated with potential social tensions, threats to public order, and concerns about national stability, while negative stigma is often amplified by media narratives. The findings demonstrate that economic and security issues are mutually reinforcing: lack of economic opportunities can escalate insecurity, while security restrictions reduce immigrants’ participation in economic life. This study emphasizes the need for comprehensive and balanced policies that ensure limited legal access to employment, strengthen security governance, and encourage inclusive social interaction. By synthesizing relevant literature, this research offers a more holistic understanding of immigrant integration in Indonesia and contributes practical insights for policy development and academic discourse.